Using nanomaterials to address SARS-CoV-2 variants through development of vaccines and therapeutics - Hangad, Maria Victoria; Keshvani, Sarah; Kelpin, Niya; Walters-Shumka, Jonathan; Hood, McKayla; Volk, Cameo; Pal, Danika; Willerth, Stephanie M. (Frontiers in Materials, 2022)
Nanomaterials have played a significant role in effectively combating the global SARS-CoV-2 pandemic through the development of vaccines as well as antiviral therapies. These versatile, tunable materials can interact with a broad range of biologically relevant molecules for preventing COVID-19 infection, generating immunity against COVID-19, and treating infected patients. These applications of nanomaterials include providing controlled therapeutic delivery for cargos including nucleic acids, proteins, or small molecules, and they can also be applied to point-of-care diagnostics, treatments focused on symptom mitigation, and disease-modelling. This review examines the existing literature on COVID-19 related nanomaterial applications, including perspective on nanotechnology-based vaccines and therapeutics, and discusses how these tools can be adapted to address new SARS-CoV-2 variants of concern. We also analyze the limitations of current nanomaterial approaches to managing COVID-19 and its variants alongside the challenges posed when implementing this technology. We end by providing avenues for future developments in this ever-evolving field.